Examining Occupational Safety and Health Awareness Behind the Hustle and Bustle of Traditional Markets: Evidence from Informal Workers in Makassar, Indonesia - A. Asran; I. Irwan (Golden Ratio of Social Science and Education, 2026)
Traditional markets in Makassar, Indonesia, are important economic hubs but also complex multi-hazard workplaces for informal workers. This study examines occupational safety and health (OSH) awareness and develops a feasible community-based intervention model. Using a mixed-method design (survey, walkthrough observations, and semi-structured interviews/participatory discussions), the study maps patterns of knowledge, attitudes, and everyday safety practices while identifying barriers in infrastructure and governance. Findings suggest that preventive routines are more consistent when actions are low-cost and compatible with fast-paced market work. Still, adoption weakens when prevention requires extra time, discomfort, or cost. Environmental constraints (wet floors and drainage, congestion points, cable management) and fragmented responsibility further reduce safety signals. The paper proposes an intervention package combining basic environmental and administrative controls, peer-based behavior reinforcement, and routine monitoring embedded in market management to reduce everyday risk and support market quality.